2021
DOI: 10.1126/sciadv.abc6160
|View full text |Cite
|
Sign up to set email alerts
|

A GWAS in Latin Americans identifies novel face shape loci, implicating VPS13B and a Denisovan introgressed region in facial variation

Abstract: To characterize the genetic basis of facial features in Latin Americans, we performed a genome-wide association study (GWAS) of more than 6000 individuals using 59 landmark-based measurements from two-dimensional profile photographs and ~9,000,000 genotyped or imputed single-nucleotide polymorphisms. We detected significant association of 32 traits with at least 1 (and up to 6) of 32 different genomic regions, more than doubling the number of robustly associated face morphology loci reported until now (from 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 86 publications
1
39
0
Order By: Relevance
“…Compared to 2D landmarks, 3D landmarks are more robust against shifting, rotation, and scaling. Compared with the studies using micro‐CT images, 3D surface images may capture additional information from facial soft tissue thickness 7 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to 2D landmarks, 3D landmarks are more robust against shifting, rotation, and scaling. Compared with the studies using micro‐CT images, 3D surface images may capture additional information from facial soft tissue thickness 7 …”
Section: Discussionmentioning
confidence: 99%
“…Compared with the studies using micro‐CT images, 3D surface images may capture additional information from facial soft tissue thickness. 7 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the reconstructed rare haplotype variant may be known to be associated with a rare phenotype [e.g. a Denisovan haplotype was recently discovered to be associated with the lip thickness ( Bonfante et al, 2021 )], in which case the phenotypes (e.g. the facial appearance) of the human subject can be inferred.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…A handful of rare variants have been identified in genes, however most are found in non-coding portions of the genome. We and others have shown that such variants are systematically enriched in sequences that obtain active chromatin states during early human craniofacial development, particularly those annotated as strong enhancers (Bonfante et al, 2021;Liu et al, 2021;Wilderman et al, 2018). Strong enhancers only active in developing craniofacial tissues were enriched for craniofacial related transcription factor (TF) binding sites and generally localized near genes implicated in craniofacial abnormalities.…”
Section: Introductionmentioning
confidence: 97%